Persepsi kepuasan nelayan payang terhadap pemanfaatan jasa tambat labuh di Pelabuhan Perikanan Nusantara Brondong Lamongan - Munir, Miftachul (Jurnal Sosial Ekonomi Perikanan, 2023)
The Indonesian government pays special attention to fishermen to create superior and competent fishermen and can become a driving force for the country's economy by way of the government providing assistance to fishermen by establishing the Ministry of Maritime Affairs and Fisheries (KKP), which provides port facilities to make it easier for fishermen. There are 4 types of fishing ports in Indonesia, such as: (1) Ocean Fishing Ports, (2) Archipelago Fishing Ports, (3) Coastal Fishing Ports, (4) Fish Landing Bases. The types of fishing ports are distinguished from the fishing intensity at the port. The analytical method is a qualitative descriptive method, stating that a qualitative descriptive method is a method used to describe or analyze a research result but not used to make broader conclusions. The number of respondents is 20 people with data collection techniques by way of interviews and using questionnaires. Data analysis with the theory of Miles and Huberman. The results obtained from X1 (Medium Infrastructure) with answers: 82.5% (the average answer is SS or Strongly Agree), 17.5%. (The average answer is S or Agree). For X2 (Mooring Administration answer: 70%. (Average answering SS), 20% (Average answering S), 10% (Average answering Disagree (TS)). Y (Satisfaction) : 70% (Average answering SS), 20% (Average answering S) 5% (Average answering RR).